Studies on chitosan based films obtained by blending with agar and poly vinyl alcohol / Esam A. Elhefian - Elhefian, Esam A. (2011)
This work deals with blends of chitosan (CS) with agar (AG) and/or polyvinyl alcohol (PVA) at different proportions in solution and solid film forms with the aim to develop biopolymer blends with established rheological, mechanical, thermal, swelling and surface properties. In the first part of this work, a number of blended solutions of (CS/AG), (CS/PVA) and (CS/AG/PVA) at different proportions (considering chitosan as the major component) were prepared. The effects of temperature, shear rate, shearing time and storage time on the rheological properties of the three blended solutions with respect to the apparent viscosity and the shear stress were investigated in correlation with the shear rate. Rheological results showed that Newtonian-like behavior was observed at temperatures from 40 to 55oC for the CS/AG blended solutions at low concentrations of AG, whereas a shear thinning behavior (pseudoplastic non-Newtonian behavior) was remarkably observed at high concentrations of AG. A Newtonian behavior was observed at the same range of temperature for all CS/PVA blended solutions with various ratios. In addition, the ternary blended solutions of CS/AG/PVA were found to display a shear thinning behavior only at high concentrations of AG and PVA. The increase in the viscosity and the appearance of shear thinning behavior with the increase in the concentration of AG in CS/AG blended solutions and both of AG and PVA in CS/AG/PVA ternary blended solutions could be due to the existence of good interaction among the components. The viscosity of the three blended solutions was found to be a function of temperature and follow Arrhenius equation. Studying the effect of shearing time on the apparent viscosity of all blended solutions did not show any significant differences at all shearing times applied in this study except the proportion 50/50 for CS/AG blended solution and the ratios containing higher concentrations than 15% of each of AG and PVA for the CS/AG/PVA ternary blended iii solutions. In addition, different behaviors were observed for the blended solutions when the period of storage was extended to three weeks. In the second part of this work, CS/AG, CS/PVA and CS/AG/PVA blended films were prepared by blending different proportions similar to those in blended solution. The chemical structure and the morphology of the obtained blended films were investigated using Fourier transform infrared (FTIR) and field emission scanning electron microscope (FESEM). The thermal stability of the blended films was also studied using thermal gravimetric analysis (TGA) and differential scanning calorimetry (DSC). Generally, it was found that CS, AG and/or PVA form highly compatible blends and their films displayed homogenous and smooth surface properties compared to their individual pure components. Studying the mechanical properties of the films showed some improvement in tensile strength (TS) with respect to CS/PVA and CS/AG/PVA blended films with respective increase in AG and /or PVA contents, but a decrease in the TS of CS/AG blended films with increasing AG content was observed. Blending of AG and/or PVA with CS at all proportions was found to enhance the swelling of the obtained films compared to the pure CS film. Static water contact angle measurements confirmed the affinity of the blended films towards water, which demonstrates that blending with AG and/or PVA can improve the wettability of the blended films. Based on the findings of this study, it can be suggested that blending of AG and/or PVA with CS brings about new biomaterials with improved tensile strength, swelling and enhanced wattability while maintaining similar thermal properties as the main component (CS).